1998
DOI: 10.1177/0146167298245004
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style and the Discussion of Shared and Unshared Information in Decision-Making Groups

Abstract: This study found that during group decision-making discussions, shared information (i.e., information held by all group members) was brought into discussion earlier, and was more likely to be mentioned overall, than was unshared information (i.e., unique information held by just one member or another). These results are consistent with a dynamic information sampling model of group discussion. It also was found that groups with a participative leader discussed more information (both shared and unshared) than gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
10

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 29 publications
2
104
1
10
Order By: Relevance
“…Whereas past research has clearly suggested that members of equal-status groups have difficulty sharing uniquely-held information (Stasser, 1999), Larson, Foster-Fishman, and Franz (1998) found that in groups with members of unequal status, status-advantaged members who adopted a more participative (i.e., socialized) style were able to encourage the expression and utilization of uniquely-held information. Higher-status members facilitated the utilization of unshared information by soliciting and then explicitly acknowledging contributions from lower-status others.…”
Section: Socialized Power and Knowledge Transfermentioning
confidence: 88%
“…Whereas past research has clearly suggested that members of equal-status groups have difficulty sharing uniquely-held information (Stasser, 1999), Larson, Foster-Fishman, and Franz (1998) found that in groups with members of unequal status, status-advantaged members who adopted a more participative (i.e., socialized) style were able to encourage the expression and utilization of uniquely-held information. Higher-status members facilitated the utilization of unshared information by soliciting and then explicitly acknowledging contributions from lower-status others.…”
Section: Socialized Power and Knowledge Transfermentioning
confidence: 88%
“…With regard to temporal patterns, shared information tends to be discussed earlier than unshared information and information discussed later in the discussion frequently has less impact on the decision (e.g., Larson et al, 1994). Social variables affecting information sharing include leadership (e.g., Larson et al, 1996Larson et al, , 1998, status (Hollingshead, 1996a), and expertise (Stasser et al, 1995). In addition, various aspects of the task environment have been found to impact the information sharing process, including information load (e.g., Stasser and Titus, 1987), intellective versus judgement tasks (e.g., Stasser and Stewart, 1992), and recall versus choice demands (e.g., Hollingshead, 1996b;Stewart and Stasser, 1998).…”
Section: Empirical Researchmentioning
confidence: 99%
“…With respect to processes within a group, different types of social dynamics lead to a less than optimal performance. These include conformity and polarization which move a group as a whole towards more extreme opinions (Ebbesen & Bowers, 1974;Mackie & Cooper, 1984;Isenberg, 1986), groupthink that leads to unrealistic group decisions (Janis, 1972), the lack of sharing of unique information so that intellectual resources of a group are underused (Larson et al, 1996(Larson et al, , 1998Stasser, 1999;Wittenbaum & Bowman, 2003) and the suboptimal use of relevant information channels in social networks (Leavitt, 1951;Mackenzie, 1976;Shaw, 1964).…”
Section: Trust Connectionist Model Of Communicationmentioning
confidence: 99%
“…With respect to processes within a group, different types of social dynamics lead to a less than optimal performance. These include conformity and polarization which move a group as a whole towards more extreme opinions (Ebbesen & Bowers, 1974;Mackie & Cooper, 1984;Isenberg, 1986), groupthink that leads to unrealistic group decisions (Janis, 1972), the lack of sharing of unique information so that intellectual resources of a group are underused (Larson et al, 1996(Larson et al, , 1998Stasser, 1999;Wittenbaum & Bowman, 2003) and the suboptimal use of relevant information channels in social networks (Leavitt, 1951;Mackenzie, 1976;Shaw, 1964).These different approaches provide a new focus for the understanding of cognition that might be summarized as collective intelligence (Levy, 1997;Heylighen, 1999) or distributed cognition (Hutchins, 1995), that is, the cognitive processes and structures that emerge at the social level. To understand collective information processing, we must consider the distributed organization constituted by different individuals with different forms of knowledge and experience TRUST Connectionist Model of Communication 4 and the social network that links them together and that supports their interindividual communication.…”
mentioning
confidence: 99%